2006
DOI: 10.1097/01.smj.0000224755.73679.67
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of the Colorectal Cancer Disparities Among Demographic Subgroups: A Spatial Analysis

Abstract: Objective: The literature suggests that colorectal cancer mortality in Texas is distributed inhomogeneously among specific demographic subgroups and in certain geographic regions over an extended period. To understand the extent of the demographic and geographic disparities, the present study examined colorectal cancer mortality in 15 demographic groups in Texas counties between 1990 and 2001. Methods:The Spatial Scan Statistic was used to assess the standardized mortality ratio, duration and age-adjusted rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Previous spatial analyses showed that CRC survival varied geographically across demographic subgroups [6, 59], but we now show that where CRC patients live may differentially impact the effect of tumor stage on survival. One mechanism by which stage at diagnosis and geography could interact to affect survival is through the biological processes of increased inflammation and oxidative stress [37].…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Previous spatial analyses showed that CRC survival varied geographically across demographic subgroups [6, 59], but we now show that where CRC patients live may differentially impact the effect of tumor stage on survival. One mechanism by which stage at diagnosis and geography could interact to affect survival is through the biological processes of increased inflammation and oxidative stress [37].…”
Section: Discussionmentioning
confidence: 48%
“…Using newly developed statistical models, evidence is starting to emerge that not everyone is affected by their residential geographic location to the same extent and that the extent of the effects of location may depend on individual characteristics [6, 2428]. However, most studies have focused on the interplay between geographic location and sociodemographic characteristics of study participants [25, 26, 28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent county-level study described changes in geographic disparities over time (Schootman et al, 2010). Also, studies in Texas showed areas where breast cancer incidence was elevated and how risk factors affected the geographic disparity in incidence (Bambhroliya et al, 2012; Hsu et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In Florida, northern and central counties exhibited the greatest racial disparities in late-stage PCa which was associated with lower censustract income and lower college education [43]. Additionally, the late-stage proportions decreased significantly from 1981 to 2007, however, the rate of decline varied greatly based on county location and racial groups [49]. This variation was suggested to be related to geographical disparities in the implementation of the Prostate Specific Antigen (PSA) screening [52].…”
Section: Gis Studies That Examined Disparities In Pca Grade and Stage...mentioning
confidence: 99%